Isotropic 3D Cartesian single breath‐hold CINE MRI with multi‐bin patch‐based low‐rank reconstruction - Küstner, Thomas; Bustin, Aurelien; Jaubert, Olivier; Hajhosseiny, Reza; Masci, Pier Giorgio; Neji, Radhouene; Botnar, René; Prieto, Claudia (Magnetic resonance in medicine, 2020)
Purpose To develop a novel acquisition and reconstruction framework for isotropic 3D Cartesian cardiac CINE within a single breath‐hold for left ventricle (LV) and whole‐heart coverage. Methods A variable‐density Cartesian acquisition with spiral profile ordering, out‐inward sampling, and acquisition‐adaptive alternating tiny golden/golden angle increment between spiral arms is proposed to provide incoherent and nonredundant sampling within and among cardiac phases. A novel multi‐bin patch‐based low‐rank reconstruction, named MB‐PROST, is proposed to exploit redundant information on a local (within a patch), nonlocal (similar patches within a spatial neighborhood), and temporal (among all cardiac phases) scale with an implicit motion alignment among patches. The proposed multi‐bin patch‐based low‐rank reconstruction reconstruction is compared against compressed sensing reconstruction, whereas LV function parameters derived from the proposed 3D CINE framework are compared against those estimated from conventional multislice 2D CINE imaging in 10 healthy subjects and 15 patients. Results The proposed framework provides 3D cardiac CINE images with high spatial (1.9 mm3) and temporal resolution (˜50 ms) in a single breath‐hold of ˜20 s for LV and ˜26 s for whole‐heart coverage in healthy subjects. Shorter breath‐hold durations of ˜13 to 15 s are feasible for LV coverage with slightly anisotropic resolution (1.9 × 1.9 × 2.5 mm) in patients. LV function parameters derived from 3D CINE were in good agreement with 2D CINE, with a bias of −0.1 mL/0.1 mL, −0.9 mL/−1.0 mL, −0.1%/−0.8%; and confidence intervals of ±1.7 mL/±3.7 mL, ±1.2 mL/±2.6 mL, and ±1.2%/±3.6% (10 healthy subjects/15 patients) for end‐systolic volume, end‐diastolic volume, and ejection fraction, respectively. Conclusion The proposed framework enables 3D isotropic cardiac CINE in a single breath‐hold scan of ˜20 s/˜26 s for LV/whole‐heart coverage, showing good agreement with clinical 2D CINE scans in terms of LV functional assessment.